Monthly triple-dose gadolinium administration: potential associations with leukopenia, hypophosphatemia, and bone marrow T1 hyperintensity. Issue 2 (February 2022) - Chen, Daniel; Wolansky, Ivan; Imitola, Jaime; Malchoff, Carl; Wu, Rong; Dhib-Jalbut, Suhayl; Bulsara, Ketan; Wolansky, Leo
Objective: Monthly scanning with triple-dose gadopentetate dimeglumine has been shown to be associated with progressive increases in bone T1 hyperintensity, hypophosphatemia, and leukopenia. This study was performed to retrospectively investigate the potential associations among these phenomena. Methods: This retrospective analysis involved patients who had received monthly triple-dose gadopentetate dimeglumine for up to 2 years as part of treatment for multiple sclerosis. Monthly magnetic resonance imaging scans of the brain (n = 67) were segmented to evaluate the signal intensity in the cranial marrow. Potential associations among the marrow T1 hyperintensity, serum phosphate concentration, and white blood cell count were examined. Results: Patients in the no leukopenia group showed a statistically significant mean monthly increase in the bone marrow signal-to-noise ratio of 0.0430/month. Patients in the leukopenia group showed a mean monthly increase in the bone marrow signal-to-noise ratio of 0.0398/month, but this was not statistically significant. Patients in the hypophosphatemia group were significantly less likely to develop leukopenia than patients who had never developed hypophosphatemia. Conclusions: Although monthly administration of triple-dose gadopentetate dimeglumine over 13 months has been associated with progressive increases in leukopenia, hypophosphatemia, and T1 signal intensity of bone, this study showed an inverse relationship between leukopenia and hypophosphatemia.